Pengembangan Desa Wisata Studi Kasus Situs Liyangan Desa Wisata Liangan - Ryan Adhinugraha Wardoyo (Syntax Idea)
Microsoft Office Translator The discovery of the Liyangan Site in Liangan Hamlet made residents form a Tourism Awareness Group in the hope of making Liangan Hamlet into a Liangan Tourism Village. Therefore, it is necessary to review the development of Liangan Tourism Village and also the impact that occurred after the discovery of the Liyangan Site because the participation of local communities is important in tourism development. Liyangan site is a unique cultural heritage because there are temples, batur, petirtaan, talud, stairs, ancient macadam roads, and ancient agricultural land. Although the Liyangan Site has been discovered since 2008, until 2022 the Liyangan Site still has not provided major changes to the economy of the residents of Liangan Hamlet. The method in this study is a qualitative descriptive method based on data collection in the form of observation and also interviews using purposive sampling techniques. The results of the study found that the development of Liangan Tourism Village is still not going well because the Liyangan Site has not been allowed to apply entrance tickets so that residents still cannot realize tour packages to improve the economy so that residents still choose to become farmers. Activities are increasingly hampered due to the COVID-19 outbreak, making activities at the Liyangan Site postponed from 2020-2022. Therefore, residents created a Cultural Kirab to increase the attractiveness of the Liyangan Site.